Web characteristics determine niche partitioning for orb-web spiders (Araneae, Tetragnathidae) in Malaysia - Dzulhelmi Muhammad Nasir; Thary Gazi Goh; Asraf Bakri; Zulqarnain Mohamed; Norma-Rashid Yusoff; Faszly Rahim (Taylor and Francis Online, 2024)
Non-Indexed Publication